Restricted Kinematics in Children With Autism in the Execution of Complex Oscillatory Arm Movements - Zhao, Zhong; Zhang, Xiaobin; Tang, Haiming; Hu, Xinyao; Qu, Xingda; Lu, Jianping; Peng, Qiongling (Frontiers in Human Neuroscience, 2021)
Restricted and repetitive behavior (RRB) is a core symptom of autism spectrum disorder (ASD) characterized by features of restrictedness, repetition, rigidity and invariance. Few studies have investigated how restrictedness is manifested in motor behavior. The present study aimed to address this question by instructing participants to perform the utmost complex movement. Twenty children with ASD and twenty-three children with typical development (TD) performed one dimensional, left-right arm oscillations by demonstrating varying amplitude and frequency. Entropy of amplitude and velocity were calculated as indices of kinematic complexity. Results showed that the velocity entropy, but not the amplitude entropy, was significantly lower in ASD than in TD (p < .01), suggesting the restricted kinematics. Further analysis demonstrated that significantly higher proportion of the velocity values was allocated at low-speed level in the ASD children (p < .01). Qualitative comparison of the complex movement with movement at preferred frequency suggested that the ASD children might be less likely to shift away from the preferred movement. However, our study can be improved in terms of recruiting a larger sample of participants, measuring the level of motivation, and collecting both complex and preferred movement of the same participant.